2014
DOI: 10.1038/srep05514
|View full text |Cite
|
Sign up to set email alerts
|

Multi-color broadband visible light source via GaN hexagonal annular structure

Abstract: Multi-color and broadband visible emission was realized thorough the hexagonal annular structure of GaN. The annular structure fabricated by selective-area growth emitted purple, blue and green color-emission from the multi-facets. The hexagonal annular structure provided various sidewalls of {101} and {112} semi-polar facets, and (0001) polar facet. From the cathodoluminescence study, the (0001) plane had the longest wavelength of 525 nm, and the {101} facet of 440 nm peak wavelength had longer wavelength emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Absolute surface energies determine the crystal growth rate and equilibrium crystal shape, leading to the famous Wulff construction [1], which is generally applicable for various semiconductor materials [2][3][4][5][6][7][8]. Additionally, absolute surface energies have close relations with the syntheses of novel nanostructures [9][10][11][12], and novel strategies of controlling crystal growths by strain or surfactants [13][14][15][16][17][18][19][20][21]. One of the major problems remains to be solved in epitaxial growth is how to determine the growth mode of the hetero-epitaxial layers [22,23], which is largely determined by the absolute surface energies of the substrate materials and the epi-layers [13].…”
Section: Introductionmentioning
confidence: 99%
“…Absolute surface energies determine the crystal growth rate and equilibrium crystal shape, leading to the famous Wulff construction [1], which is generally applicable for various semiconductor materials [2][3][4][5][6][7][8]. Additionally, absolute surface energies have close relations with the syntheses of novel nanostructures [9][10][11][12], and novel strategies of controlling crystal growths by strain or surfactants [13][14][15][16][17][18][19][20][21]. One of the major problems remains to be solved in epitaxial growth is how to determine the growth mode of the hetero-epitaxial layers [22,23], which is largely determined by the absolute surface energies of the substrate materials and the epi-layers [13].…”
Section: Introductionmentioning
confidence: 99%
“…(0001) flat top plane, the {1120} vertical facet, and the {1122} inclined facet. After 60 minute, these various facets merged laterally to (0001) flat plane because the growth rate of GaN on (0001) plane was slower than on other facets [14]. The result demonstrates that the lateral growth of GaN was enhanced at 1040 o C under 500 torr.…”
Section: Resultsmentioning
confidence: 84%
“…The final equilibrium shape of faceted structure is determined by the growth rate of each facets. It was reported that the truncated structure was followed to the convex growth mode in which the facets of fast growth rate became to diminish and the facets of slow growth rate became to dominate [21,24]. Because the GaN faceted structure grown at 950°C had higher vertical growth rate (G (0001) E2.5 μm/ h, { } G 1122 E0.5 μm/h), the equilibrium shape of the faceted structure became to triangular stripes structure.…”
Section: Resultsmentioning
confidence: 99%
“…Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jcrysgro to obtain crack-free AlGaN over whole wafer based on our previous study of faceted structures grown on a selective-area mask [21]. The SAG method might be suitable way to obtain high quality AlGaN of large area with reducing dislocations and strain due to the controllable shape and size of the faceted structure.…”
Section: Introductionmentioning
confidence: 99%